Lateral DNA transfer : mechanisms and consequences - Bushman, Frederic (Cold Spring Harbor Laboratory Press, 2002)
This text is about mobile genes - the transfer of DNA between unrelated cells. This well-illustrated volume discusses the machinery of gene transfer and its wide-ranging biological biological and health consequences.